2022
DOI: 10.1002/chem.202202227
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorescent Bimetallic C^C* Platinum(ii) Complexes with Bridging Substituted Diphenylformamidinates

Abstract: A series of phosphorescent bimetallic platinum(II) complexes is presented, which were synthesized by the combination of bidentate cyclometalated N-heterocyclic carbene ligands and different bridging diphenylformamidinates. The complexes were characterized by standard techniques and additionally two solid-state structures could be obtained. Photoluminescence measurements revealed the strong emissive behavior of the compounds with quantum yields of up to 90 % and emission lifetimes of approx. 2 μs. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 85 publications
0
8
0
8
Order By: Relevance
“…The monometallic complexes 4 and 5 with the identical MPI ligand show a hypsochromic shift of 83/84 nm respectively in comparison to the bimetallic complexes 3‐trans/cis . Different substituents on the aryl ring of the amidinate ligand have shown to have a distinct but comparatively small influence on the emission wavelength of bimetallic C^C*‐cyclometalated platinum(II) formamidinate complexes [57] . Therefore the strong shift towards shorter emission wavelengths is mainly a consequence of the missing metal‐metal interactions and demonstrates the uniqueness of this class of monometallic C^C* cyclometalated platinum(II) amidinate complexes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The monometallic complexes 4 and 5 with the identical MPI ligand show a hypsochromic shift of 83/84 nm respectively in comparison to the bimetallic complexes 3‐trans/cis . Different substituents on the aryl ring of the amidinate ligand have shown to have a distinct but comparatively small influence on the emission wavelength of bimetallic C^C*‐cyclometalated platinum(II) formamidinate complexes [57] . Therefore the strong shift towards shorter emission wavelengths is mainly a consequence of the missing metal‐metal interactions and demonstrates the uniqueness of this class of monometallic C^C* cyclometalated platinum(II) amidinate complexes.…”
Section: Resultsmentioning
confidence: 97%
“…[53,54] In previous studies N,N'-diphenylamidinate ligands were shown to form dimeric complexes when combined with a C^C* cyclometalated platinum(II)-center that exhibited interesting photoluminescent properties. [55][56][57] With respect to the application in OLED devices these bimetallic complexes are less economical than their monometallic counterparts due to the higher precious metal content. Furthermore, this class of bimetallic complexes is known for its excellent quantum yields and fast radiative decay times, but shows a bathochromic shift of the emission wavelength due to metallophilic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Chemie Forschungsartikel onswellenlänge, die mit einer Verlängerung der Phosphoreszenzlebensdauer des angeregten Zustands einhergeht. Die bimetallischen Komplexe 3-trans und 3-cis zeigen ähnliche Eigenschaften wie bereits bekannte bimetallische Platin(II)-Formamidinatkomplexe, [55][56][57] wohingegen die monometallischen Komplexe Emissionswellenlängen im blauen (4 und 5) bis grün-blauen (6 und 7) Bereich des sichtbaren Spektrums sowie Quantenausbeuten von 18-87 % aufweisen. Folglich wird die Eignung sterisch anspruchsvoller Formamidinate als Hilfsliganden für zyklometallierte C^C*-Platinkomplexe in Photolumineszenzanwendungen belegt.…”
Section: Methodsunclassified
“…N,N'-Diphenyl-, N,N'-Bis (2,4,6-trimethylphenyl)-und N,N'-Bis(2,6-diisopropylphenyl)-Formamidinat wurden als Modellliganden mit unterschiedlichem Grad an sterischem Anspruch ausgewählt. Weitere, am Arylring substituierte Formamidinate, von denen die Bildung bimetallischer Komplexe bekannt ist, [55][56][57][58] wurden ebenfalls zu Vergleichszwecken berechnet. Die erhaltenen freien Reaktionsenthalpien (Tabelle 1) zeigen, dass der monometallische Komplex mit zunehmender Größe der Substituenten (von Phenyl-zu 2,6-Diisopropylphenyl-) energetisch günstiger wird, während periphere Substituenten keinen nennenswerten Einfluss haben (Tabelle S1, vollständige Angaben zu den Dichtefunktionaltheorie-(DFT)-Berechnungen finden sich in den Hintergrundinformationen).…”
Section: Synthese Und Charakterisierungunclassified
See 1 more Smart Citation